844 Reye's Syndrome and Disseminated Intravascular Coagulation Presented by Rotavirus Infection. (October 2012) - Yalaki, Z; Arikan, FI; Buyukyilmaz, G; Altan, B; Demir, H; Bilge, Y Dallar
Abstract : Rotavirus is one of the leading causes of severe gastroenteritis in childhood, which is an infection known to be limited to the gastrointestinal system. However, a case of extra-intestinal complication developed during rotavirus gastroenteritis is presented here. Case: A five years old patient with febrile convulsion, also having complaints of vomiting, diarrhea, and fever was brought to our hospital. General condition of the patient was bad; she was unconscious and severely dehydrated. Her laboratory findings showed acidosis and renal failure; coagulation tests showed impairment. During her monitoring, gastrointestinal bleeding, increase in liver function test values, hyperammonemia, neutropenia, and hypoglycemia were developed. Rotavirus antigen was found to be positive in the gaita test. Patient's general condition was improved by giving antibiotics, liquids, fresh frozen plasma, and thrombocites in the early stages after which she was discharged. Close monitoring of patients with rotavirus gastroenteritis in terms of extra-intestinal complications and applying appropriate treatment in the early stages may save lives.